2019
DOI: 10.1007/s12178-019-09590-2
|View full text |Cite
|
Sign up to set email alerts
|

UCL Injury in the Non-throwing Athlete

Abstract: Purpose of Review Primarily reported in the overhead throwing athlete, ulnar collateral ligament (UCL) injuries have been extensively studied since Dr. Frank Jobe first described his technique for ulnar collateral ligament reconstruction on professional baseball pitcher Tommy John. While the framework for our understanding of UCL injury was initially established studying the repetitive valgus loading of the throwers' elbow, other sport-related activities in non-throwing athletes can impart similar valgus stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…While the vast majority of UCL injuries occur in the throwing athlete, studies have found that other athletes such as football players, gymnasts, tennis players, and wrestlers have undergone reconstructions. In nonathlete populations, although nonoperative management can successfully treat UCL injuries, surgical intervention has also high rates of success and return to activity, especially populations not partaking in overhead athletic activities 13 . As the number of UCL injuries increases, it is important to improve upon the available techniques for UCLR to optimize the performance of these reconstructions and potentially shorten the recovery time after surgery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the vast majority of UCL injuries occur in the throwing athlete, studies have found that other athletes such as football players, gymnasts, tennis players, and wrestlers have undergone reconstructions. In nonathlete populations, although nonoperative management can successfully treat UCL injuries, surgical intervention has also high rates of success and return to activity, especially populations not partaking in overhead athletic activities 13 . As the number of UCL injuries increases, it is important to improve upon the available techniques for UCLR to optimize the performance of these reconstructions and potentially shorten the recovery time after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…In nonathlete populations, although nonoperative management can successfully treat UCL injuries, surgical intervention has also high rates of success and return to activity, especially populations not partaking in overhead athletic activities. 13 As the number of UCL injuries increases, it is important to improve upon the available techniques for UCLR to optimize the performance of these reconstructions and potentially shorten the recovery time after surgery. UCLR using either palmaris longus (PL) or gracilis (GR) tendons is the mainstay of treatment for UCL injuries that fail to improve with rest and physical therapy.…”
mentioning
confidence: 99%
“…§ The literature is surprisingly scarce on clinical outcomes after UCL surgery in nonthrowing athletes. 21,24,28,33 These few studies often contain small numbers of nonthrowing athletes with variable outcomes. Jones et al 17 included 3 gymnasts in their publication on UCL reconstruction using the docking technique; their study had a total of 55 athletes, with the remainder being baseball players (n = 47) and javelin throwers (n = 5).…”
Section: Discussionmentioning
confidence: 99%
“…15 Recent literature has demonstrated improvements in the surgical technique and expected outcomes after UCL surgery. 1-12,16-37 Most publications have involved baseball players, who perform repetitive overhead motions that create chronic valgus stress on the UCL. § Repetitive high loads applied to the UCL during throwing may lead to serious injury, as described in previous biomechanical studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation